Pencabutan PPKM dan risk-return industri pariwisata - Runtu, Felix; Rengkung, Clarissa (Yayasan Widyantara Nawasena Raharja, 2023)
On December 30, 2022, the Indonesian Government officially lifted the Implementation of Restrictions on Community Activities (or PPKM). This study aims to analyze the risk-return trade-off and growth of stocks in the tourism industry. The sample used was 42 stocks in the tourism business sector throughout the period 30 December 2022 to 28 April 2023 or the period after the revocation of PPKM. The findings show that 32 stocks had not achieved optimal risk-return trade-off and growth throughout the observation period. However, this study also finds that 4 stocks had a better risk-return trade-off and 5 stocks had positive growth. These findings imply that the repeal of PPKM tends to have a positive impact on tourism industry shares even though not all of them have achieved optimal performance due to the impact of the COVID-19 pandemic.